Relation of plasmid DNA and larvicide activity in indigenous Bacillus sphaericus strains - DUSSÁN, JENNY; ANDRADE, DIANA; LOZANO, LUCÍA (Revista Colombiana de Entomología, 1997)
It was determined that 18 indigenous strains of Bacillus sphaericus (Bs) highly toxic (80-100 %) to third instar larvae of Culex quinquefasciatus had high molecular weight plasmids, and in order to associate the strains toxicity with the presence of these plasmids, it was done treatment with curing agents, like temperature and acridine orange. For the curing with temperature, it was cultured the strains at 40-41°C and for acridine orange, it was tested differents concentrations that were permissive for bacilli growth (20-100 ptg/ m1). In order to confirm the curing of the strains that were treated it was done a plasmid DNA preparation and agarose gel electrophoresis. The toxicity loss of the cured strains was evaluated by biological assays against Culex quinquefasciatus larvae. Of the 18 strains of B sphaericus studied at the beginning 5 were cured with temperature, and in this study 8 were cured with acridine orange and in 3 strains the plasmid remained. The bacilli that lost their plasmid continued been pathogenic for larvae which indicate that the genes involucrated in toxicity belong to the chromosome. There were found differences among the strains with respect to the resistance to curing agents and in general, it was observed great stability of the plasmids.